The Effect of Music Therapy in Reducing Dental Anxiety and Lowering Physiological Stressors - Wazzan, Mohammad; Estaitia, Mohammed; Habrawi , Sima; Mansour, Dina; Jalal, Zain; Ahmed, Hadir; Hasan, Hayder A.; Al Kawas, Sausan (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The anxiolytic effects of music have been studied during the past twenty years in different medical therapies. The aim of this study is to evaluate the effect of music therapy on patients’ dental anxiety, salivary cortisol, heart rate, blood pressure and body temperature during dental treatment. Methods: In this randomized control study, 46 patients were randomly selected from the Urgent Care dental clinic who needed urgent endodontic treatment (endodontic access and pulp extirpation). Participants were divided into two groups: intervention group (N=23) which was exposed to slow rhythm melody music and had no lyrics throughout the entire procedure and a control group (N=23) who undergoes the same dental procedure without being exposed to music. Participants’ blood pressure, heart rate, body temperature and salivary cortisol were measured before and after the treatment for both groups. Results: Patients in the intervention group showed lower salivary cortisol, blood pressure, heart rate and body temperature compared to those in the control group, however, the differences did not reach to statistical significance. Conclusion: Despite the change in the dental anxiety and stress during treatment with music, the findings of this study could not establish evidence of the effect of music in reducing dental anxiety and lowering physiological stressors. Therefore, further studies with larger sample size may be needed. (www.actabiomedica.it)